Dickensian Eponyms. (1st June 2013) - Abel, Ernest L
<x xml:space="preserve">Abstract</x> Charles Dickens created almost a thousand fictional characters, many of whom have become synonyms for distinctive types of people or their pecu- liar traits. This article surveys seventeen Dickensian eponyms, cites their first appearance as such, and provides examples of their usage in magazines, books, and the Internet.